Evaluation Of Direct Ozone Depuration On Shelf-Life Of Fresh Tropical Oysters (Crassostrea Iredalei) - Teoh, Qi Yin (Universiti Sains Malaysia, 2021)
Direct ozone depuration is a potential post-harvest processing method used to treat fresh tropical oysters to ensure the safety and preserve the quality of tropical oysters especially those that are usually being eaten raw. The quality of the tropical oysters undergoes treatment was significantly affected by different levels of ozone concentration and depuration time. The present study successfully proved that higher ozone concentration and longer depuration time significantly reduced the microbial loads and slow down protein degradation while maintaining the freshness and preventing the spoilage of tropical oysters. The bacteria species present in tropical oysters reduced at a different rate due to the different initial microbial loads, variation of chemical composition in tropical oysters, sensitivity or persistency of bacteria species towards ozone and inherent differences in bacteria cells. Fecal coliforms and Vibrio cholerae showed less sensitivity towards ozone treatment than other bacteria species in this study. Despite this, higher ozone concentration and longer depuration had a detrimental effects on the survival of tropical oysters whereby the shelf-life of treated tropical oysters was shortened as compared to the fresh tropical oysters.